Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan Pada Toserba Surya Pamanukan - Jeny Dewi Sry (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This study aims to determine and analyze the effect of job training on employee performance at the Surya Pamukan department store. This research was conducted on 30 respondents using one type of research, namely explanatory research through distribution of questionnaires, while the data sources were primary and secondary data. In proving the effect of the independent variable on the dependent variable, a multiple linear regression analysis model is used. The results of this study indicate that the independent variables of job training which consist of training objectives, training participants, training instructors, training materials and training methods show that simultaneously the independent variables have a significant effect on the dependent variable, namely employee performance. Job training is a whole activity to provide, obtain, improve, and develop work competence, productivity, discipline, attitude and work ethic at a certain skill and expertise level in accordance with the level and qualifications of the position or job. The training program will affect employee performance and the level of employee attainment. Because training will improve employee performance in carrying out their job duties, so that in the end it will increase the quantity and quality of employees.